Malaysian Residential Property: A forecasting model / Nur Atiqah Khailizan, Noor Fitrah Nabilah Ismail and Nur Alia Farhana Muhammad Harith Fadzillah - Khailizan, Nur Atiqah; Ismail, Noor Fitrah Nabilah; Muhammad Harith Fadzillah, Nur Alia Farhana (2019)
Malaysia has faced a problem where Malaysian cannot afford to own a house as the prices of the house has increase along with the increasing cost of living. This study is to identify the elements that affect the housing prices in Malaysia and develop a suitable forecasting model for this issue. The last objective is to determine the best forecasting model to forecast future property prices in Malaysia. The main variables used in this study is house price and macroeconomic variables such as GDP, interest rate, CPI and geographical variable which is population. This study used a secondary data from 1990 until 2017 obtained from The Valuation and Property Service Department (2018) and The World Bank (2017). The methodology used in resolving the objective are Unit Root Test, Johansen Coi ntegration Test, Granger Causality Test and lastly Box-Jenkins Method. The results showed a relationship between house price and interest rate only based on Granger Causality Test. It can be concluded that ARIMA( 1,2, I) is the best forecasting model for future use based on analysis made using Box-Jenkins Method.